THE EFFECT OF PROPERTY MARKET VALUE, PROPERTY TYPE, PROPERTY LOCATION AND LOAN-TO-VALUE RATIO ON THE RECOVERY RATE OF NON-PERFORMING LOANS:A Case Study at PT Bank Negara Indonesia (Persero), TbkAt Regional Office 16, Papua - Irwin Niko Winardy Parasian Hutapea; Elisabet Siahaan; Handy Octavianus (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
The rise in the risk of non-performing loans (NPLs) highlights the importance of optimising the quality of property collateral to improve loan recovery rates. This study aims to analyse the influence of property market value, property type, property location and loan-to-value (LTV) ratio on the recovery rate of non-performing loans at PT Bank Negara Indonesia (Persero) Tbk Regional Office 16 in Papua. The study employs a quantitative approach using multiple linear regression. A sample of 100 data points was selected from a population of 192 using purposive sampling. The data used were secondary data in the form of loan-level data on non-performing loans sourced from the internal records of BNI Regional Office 16 in Papua. The results of the study indicate that Property Market Value and Property Location have a positive and significant effect on the Recovery Rate of Non-Performing Loans, whilst Loan-to-Value (LTV) has a negative and significant effect. Meanwhile, Property Type does not have a significant effect on the Recovery Rate of Non-Performing Loans. Property Market Value is the variable with the most dominant influence on the Recovery Rate of Non-Performing Loans. Furthermore, the results of the simultaneous test indicate that Property Market Value, Property Type, Property Location and Loan-to-Value (LTV) collectively have a significant effect on the Recovery Rate of Non-Performing Loans. These findings underscore the importance of the economic value of collateral, the quality of the property’s location and the management of the LTV ratio in supporting the effectiveness of non-performing loan recovery and strengthening banking risk management strategies.